Joint Scientific Consultation Eligibility Criterion: Hubris or Naïveté - Mondher Toumi; Bruno Falissard; Laurent Boyer; Pascal Auquier (Journal of Market Access & Health Policy)
The eligibility criteria for Joint Scientific Consultation (JSC) raise important questions about the approach taken by the Member State Coordination Group on Health Technology Assessment (HTACG) [...]